The Influence of the Cycle 5E's Learning Model on Students' Critical Thinking Ability - Nasution, Ahmad Maulana; Adlini, Miza Nina (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Education is a learning process in which students welcome and master knowledge. The ability to know the importance of skills that are very important and very important in all aspects of life, especially in education. This study aims to determine the effect of the 5E learning cycle learning model on the critical thinking ability of the Senior High School of Second grade (XI MIA class) SMA Negeri 1 Batangkuis students. This research is a quasi-experimental study in which the research population consists of two class students at SMA Negeri 1 Batang Kuis, namely class XI MIA1 as the experimental class and XI MIA2 as the control class, each of which contains 31 and 29 people. Data collection techniques in the form of critical thinking test results that refer to cognitive learning tests in the form of multiple choice questions as many as 20 questions. The sampling technique of this study used cluster random sampling, namely random sampling which was calculated using covariance analysis. The results of this study gained a data significance of 0.000 <0.05, meaning there is an effect of linear discrimination on critical thinking skills. Hopefully, we can develop vital thought skills by increasing the concentration of learning together to build ideas and keep students active in the classroom